2018
DOI: 10.1002/brb3.948
|View full text |Cite
|
Sign up to set email alerts
|

High expression of the HMGB1–TLR4 axis and its downstream signaling factors in patients with Parkinson's disease and the relationship of pathological staging

Abstract: ObjectiveTo detect the expression of high‐mobility group box protein 1 (HMGB1) and toll‐like receptor 4 (TLR4) and their downstream signaling factors—myeloid differentiation factor 88 (MyD88), nuclear factor kappa B (NF‐κB), and tumor necrosis factor alpha (TNF‐α)—in the sera of patients with Parkinson's disease (PD) in order to evaluate the relationship of the HMGB1–TLR4 axis with PD development and progression.MethodsThe serum HMGB1 and TLR4 protein levels of 120 patients with PD and 100 healthy volunteers w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 23 publications
3
32
0
Order By: Relevance
“…Fujita et al found that intracerebroventricular injection of HMGB1 could enhance the secretion of pro-inflammatory factors in brains of mice (Fujita et al, 2016). Clinical study also reported that both expression of HMGB1 and TLR4 was remarkably up-regulated in PD patients compared with healthy controls, together with that the activation of NF-kB pathway and TNF-a level were positively correlated with high expression of the HMGB1/TLR4 axis (Yang et al, 2018). Mechanically, once astrocytes and microglia are activated, the released HMGB1 will further facilitates the activation of microglia to form a vicious circle via HMGB1/TLR4/NF-kB axis, thereby accelerating the neuroinflammatory responses in brains (Gao et al, 2011).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Fujita et al found that intracerebroventricular injection of HMGB1 could enhance the secretion of pro-inflammatory factors in brains of mice (Fujita et al, 2016). Clinical study also reported that both expression of HMGB1 and TLR4 was remarkably up-regulated in PD patients compared with healthy controls, together with that the activation of NF-kB pathway and TNF-a level were positively correlated with high expression of the HMGB1/TLR4 axis (Yang et al, 2018). Mechanically, once astrocytes and microglia are activated, the released HMGB1 will further facilitates the activation of microglia to form a vicious circle via HMGB1/TLR4/NF-kB axis, thereby accelerating the neuroinflammatory responses in brains (Gao et al, 2011).…”
Section: Discussionmentioning
confidence: 89%
“…The overactivation of high mobility group box 1 (HMGB1)/ toll-like receptor 4 (TLR4) axis has been recognized as an important signaling pathway in inflammatory responses (Andersson et al, 2018). It has been reported that HMGB1 and TLR4 were highly expressing in the peripheral blood of PD patients compared with that in healthy controls (Yang et al, 2018), which demonstrated that an overaction of the HMGB1/ TLR4 axis plays an essential role in PD development.…”
Section: Introductionmentioning
confidence: 99%
“…The role of the HMGB1-TLR4 axis is very important in the pathogenesis of PD. The serum HMGB1 and TLR4 protein levels were significantly elevated in PD patients and correlated with the PD stages ( 79 ). In a rat model of PD, an anti-HMGB1 monoclonal antibody inhibited inflammation by maintaining the BBB and reducing the secretion of inflammatory cytokines, such as IL-1β and IL-6 ( 80 ).…”
Section: Damps In Neurodegenerative Diseasesmentioning
confidence: 99%
“…The activation of TLR4 by saturated fatty acids is an important mechanism potentially underlying the initiating effect of obesity on chronic low-grade inflammation. Moreover, certain actions of HMGB1 are mediated via TLRs [28][29][30]. TLR4 is the receptor of HMGB1, which induces NF-κB activation and increases the production and release of cytokines, when HMGB1 combines with TLR4 on the surface of the immune cell membrane [31].…”
Section: Endocrine Journal Advance Publicationmentioning
confidence: 99%